- The Last Wall in the Spice Land: The Dutch East Indies Facing Japanese Attack 1942: Tembok Terakhir Di Negeri Rempah: Hindia Belanda Menghadapi Serangan Jepang 1942 - Muhammad Willdan Zainur Rifai; Mukhamad Shokheh (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to explain the problems of the Dutch East Indies on the island of Java when defending against the Japanese attack. In this writing, historical research methods are used, namely heuristics, source criticism, interpretation and historiography. The sources obtained mostly come from books and newspapers, primary sources such as archives cannot be found except for photos. This research was written to provide an overview of the conditions in the Dutch East Indies, especially on the island of Java, when they were under siege by Japanese troops. This article also explains how the battle in the Java Sea took place between the Dutch East Indies fleet and the Japanese fleet. The result of this research is a writing that explains the conditions on the island of Java when it was besieged by Japan, and what is new is that data was obtained that was not exposed in newspapers and then collected to become one writing. Likewise, regarding the Java Sea Battle, the novelty comes from books that are not available in Indonesia and I combine it with several local newspaper and book sources